2019
DOI: 10.3126/forestry.v16i0.28354
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Birds in the Foothills of Phulchoki Hill, Lalitpur, Nepal

Abstract: Bird survey was conducted in Phulchoki hill during two different seasons in January 2018 and April 2018. The objective of the study was to identify seasonal avian diversity, and to determine relative abundance and species richness. Fixed radius point- count method was used to evaluate the bird diversity and their number. Shannon-Weiner Diversity Index was used to calculate the diversity of species during two different seasons. A total of 78 species of birds belonging to 7 orders and 24 families were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Studies have found variation in species diversity among different regions of Nepal. For example, Jha (2019) observed 78 bird species belonging to seven orders and 24 families in the foothills of Phulchoki Hill. Pandey et al (2020) recorded 112 species belonging to 13 orders and 35 families in the Mardi Himal trekking region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found variation in species diversity among different regions of Nepal. For example, Jha (2019) observed 78 bird species belonging to seven orders and 24 families in the foothills of Phulchoki Hill. Pandey et al (2020) recorded 112 species belonging to 13 orders and 35 families in the Mardi Himal trekking region.…”
Section: Introductionmentioning
confidence: 99%
“…(2016). This contrasts with the observations ofPawar et al (2011), Jha (2019,Pandey et al (2020),Venkitachalam and Vijayan (2020),Paliwal et al (2021),Shah & Sharma (2022), and Withaningsih et al (2022), who found other families being more numerous than Accipitridae. The Pokhara valley is regarded as a hub for birds of prey because it harbours large numbers of resident raptor species…”
mentioning
confidence: 59%
“…However, during the winter season, the assemblage of water bird species was high because most of the winter migratory birds are dependent on the wetland. This might be because Chitwan National Parks being located in warmer region, the winter migratory birds feel more comfortable in warmer region due to the harsh cold climatic conditions of the cold mountainous regions and colder parts of the world during winter (Jha, 2019). The birds which come to Nepal as winter migrants comprise mostly Duck species and Raptors, the other species are Thrushes, Flycatchers, Leaf Warblers, and Wagtails (Jha, 2018).…”
Section: Discussionmentioning
confidence: 99%